Burden of cancer and human exposure to chemicals. (30th September 2020) - Carvalho, R; Randi, G; Martos, C; Dyba, T; Giusti, F; Nicholson, N; Neamtiu, L; Dimitrova, N; Bettio, M
Abstract: Cancer has important impacts on the EU's health systems and economies, with around 3 million new patients diagnosed each year. However, up to 40% of cancers are attributed to preventable causes. For these reasons, cancer is one of the main priorities of the EC in the health domain. The new Europe's Beating Cancer Plan of the EC, to be launched at the end of 2020, aims to support EU Member States to improve cancer control and care, by proposing actions at every key stage of the disease: prevention (lifestyle, pollution, vaccination), diagnosis, treatment and survivorship. Reliable cancer statistics are essential to propel both epidemiological research and political decision making, and provide the supporting evidence to allow assessment of best practices in all those key stages. To this purpose, the European Cancer Information System (ECIS), built on European population-based cancer registries' data, provides the latest information on indicators that quantify the burden of cancer in Europe. It permits the exploration of geographical patterns and temporal trends of incidence, mortality and survival by granting access to harmonised and validated cancer incidence data. Population-based cancer registries have been essential in many of the epidemiological studies that led to the identification of several carcinogens in the work place as well as those linked to certain lifestyle habits such as tobacco and alcohol consumption. However, In conditions of low exposure, the identification of cancer hazards has remained largely inconclusive, due to the unavailability of sufficient exposure data and appropriate models that can account for multiple exposures over extended periods. The linkage between cancer registries data and administrative databases, biobanks, environmental data and extensive lifestyle questionnaires could help identifying or consolidate the available information on emerging carcinogens and populations at risk, thus allowing the development of preventable measures.